Translation and global Asia : relocating networks of cultural production - Kwan, Uganda Sze-pui; Wong, Lawrence Wang-chi (Asian translation traditions series, 2014)
Translation and Global Asia: Relocating Cultural Production Network explores the richness of non-Western discourses and practices of translation, focusing on translational exchanges among non-Western languages and Asian translation traditions. The volume provides insight into the translation traditions of various Asian countries and addresses literary translation, translation history, and translation and colonialism.